Design of interval type-2 fuzzy precompensated PID controller applied to two-DOF robotic manipulator with variable payload. (June 2019) - Gaidhane, Prashant J.; Nigam, Madhav J.; Kumar, Anupam; Pradhan, Pyari Mohan
Abstract: The interval type-2 fuzzy logic controller (IT2-FLC), with footprint of uncertainty (FOU) in membership functions (MF), has increasingly recognized for controlling uncertainties and nonlinearities. Within the ambit of this, the efficient interval type-2 fuzzy precompensated PID (IT2FP-PID) controller is designed for trajectory tracking of 2-DOF robotic manipulator with variable payload. A systematic strategy for optimizing the controller parameters along with scaling factors and the antecedent MF parameters for minimization of performance metric integral time absolute error (ITAE) is presented. Prominently, recently proposed optimization technique hybridizing grey wolf optimizer and artificial bee colony algorithm (GWO–ABC) is utilized for solving this high-dimensional constrained optimization problem. In order to witness effectiveness, the performance is compared with type-1 fuzzy precompensated PID (T1FP-PID), fuzzy PID (FPID), and conventional PID controllers. More significantly, the robustness of IT2FP-PID is examined for payload variation, model uncertainties, external disturbance, and noise cancellation. After experimental outcome, it is inferred that IT2FP-PID controller outperforms others and can be referred as a viable alternative for controlling nonlinear complex systems with higher uncertainties. Graphical abstract: Highlights: The efficient interval type-2 fuzzy precompensated PID (IT2FP-PID) controller is presented for trajectory tracking of 2-DOF robotic manipulator with variable payload. The systematic strategy to tune the various controller parameters, scaling factors, and MF structures ofIT2FP-PID is presented using recently proposed hybrid GWO–ABC algori-thm. The comprehensive trajectory tracking analysis in terms of performance index ITAE of the IT2FP-PID controller is carried out and compared to existing T1FP-PID, FPID, and classical PID controllers. The efficacy of proposed controller is validated through exhaustive robustness analysis in presence of distinct nonlinear dynamics such as (i) payload variations, (ii) model uncertainties, (iii) disturbance in signals, and (iv) random noise at feedback path.